Bounds on Riesz Means of the Eigenvalues for Baouendi–Grushin Type Operators - Alaa Aljahili; Ari Laptev (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to consider spectral inequalities of a class of Baouendi–Grushin type operators in cylinders. Such operators are hypoelliptic and we obtain non-Weyl type inequalities depending on the rate of the degeneracy. We also give an example where all eigenvalues and eigenfunctions are computed explicitly.